Application of Certainty Factor Method to Web-based Expert System for Chicken Disease Diagnosis - Adam Ridwan; M Mahaputra Hidayat; Rifki Fahrial Zainal; Rahmawati Febrifyaning Tias; Rangsang Purnama; Akhmad Najmul Irfani; Noer Firda Yuana Ridhawaty (JEECS (Journal of Electrical Engineering and Computer Sciences), 2023)
This research aims to design an expert system to diagnose diseases in chickens. This system is designed to assist farmers in identifying diseases in chickens accurately and quickly. This expert system was built using the Certainty Factor method. Chicken disease data is collected from trusted sources, and rules are made to support the diagnostic process. This application is used to assist users in identifying chicken diseases based on the symptoms they input. This expert system is tested to see its ability to provide accurate and useful diagnosis for users. Therefore, this expert system of chicken disease diagnosis can be a useful solution in the field of animal husbandry.